2022
DOI: 10.1039/d2ta01935c
|View full text |Cite
|
Sign up to set email alerts
|

A single-atom vanadium-doped 2D semiconductor platform for attomolar-level molecular sensing

Abstract: Semiconducting materials offer promising opportunities as an ideal platform for localized surface plasmon resonance (LSPR)-free surface-enhanced Raman spectroscopy (SERS)-based molecular detection. However, conventional semiconductor-based SERS substrates have various drawbacks that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Element doping is another promising method to optimize the SERS performance of semiconductor substrates by energy band engineering. 148–152 Yang et al found that Mo-doped Ta 2 O 5 substrate could exhibit a remarkable SERS sensitivity with an EF of 2.2 × 10 7 and a low LOD 9 × 10 −9 M for methyl violet (MV) molecules under the 532 nm laser excitation (Fig. 4B).…”
Section: Single-component Sers-active Nanomaterialsmentioning
confidence: 99%
“…Element doping is another promising method to optimize the SERS performance of semiconductor substrates by energy band engineering. 148–152 Yang et al found that Mo-doped Ta 2 O 5 substrate could exhibit a remarkable SERS sensitivity with an EF of 2.2 × 10 7 and a low LOD 9 × 10 −9 M for methyl violet (MV) molecules under the 532 nm laser excitation (Fig. 4B).…”
Section: Single-component Sers-active Nanomaterialsmentioning
confidence: 99%
“…Park also represented a single-atom vanadium-doped 1T′ ReSe 2 (VSADReSe 2 ), which obtained attomolar level (10 −18 M) LOD for R6G molecules and effectively improved the SERS sensitivity. 95 The unique crystal and electronic structure of the VSADReSe 2 substrate enabled the enhanced coupling interaction and efficient CT resonance with molecules, leading to ultrahigh sensitivity with an attomolar detection limit. Moreover, this substitutional doping method employed for preparing the VSADReSe 2 demonstrated excellent operational stability and universal detection capability.…”
Section: Driving Forces For Sers Of 2d Nanomaterialsmentioning
confidence: 99%
“…As seen by the FDTD simulation, the hybrid platform demonstrated the best maximum local e-field intensity by the plasmon resonance excitation due to the unique AuPd core-shell structure as well as high-density background Au NP coupling [ 16 ]. It is worth noting that the high-density background Au NPs can largely increase the hotspot density and interaction cross-section with the R6G molecules [ 16 , 33 , 49 ]. In this regard, a large number of hotspots and strong local electromagnetic fields can be generated by the laser irradiation, which can effectively boost the charger transfer from the AuPd HyCoS NPs to R6G molecules, suggesting a significantly amplified SERS response by the EM enhancement [ 44 , 50 ].…”
Section: Sers Analyses Of Rhodamine 6g On Various Substratesmentioning
confidence: 99%